2013
DOI: 10.1016/j.freeradbiomed.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Implications of autophagy for vascular smooth muscle cell function and plasticity

Abstract: Vascular smooth muscle cells (VSMCs) are fundamental in regulating blood pressure and distributing oxygen and nutrients to peripheral tissues. They also possess remarkable plasticity, with the capacity to switch to synthetic, macrophage-like or osteochondrogenic phenotypes when cued by external stimuli. In arterial diseases such as atherosclerosis and restenosis, this plasticity appears to be critical, and depending on the disease context, can be deleterious or beneficial. Therefore, understanding the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 173 publications
(193 reference statements)
2
60
0
Order By: Relevance
“…6). In accord, previous studies have shown that autophagy is involved in the function and plasticity of VSMCs [34,35]. Interestingly, everolimus has not demonstrated significant effects on the expression of ATG5, indicating that everolimus may induce autophagy of VSMCs in an ATG5-independent way.…”
Section: Discussionsupporting
confidence: 81%
“…6). In accord, previous studies have shown that autophagy is involved in the function and plasticity of VSMCs [34,35]. Interestingly, everolimus has not demonstrated significant effects on the expression of ATG5, indicating that everolimus may induce autophagy of VSMCs in an ATG5-independent way.…”
Section: Discussionsupporting
confidence: 81%
“…30 Further, studies on human primary aortic SMCs revealed that exposure of SMCs to oxidized LDL induced not only the expression of autophagy markers but also the expression of phagocytic markers. 31 SMCs transition from a contractile to a migratory and synthetic phenotype, reflected by a typical loss of SMCs markers, such as SMC-α-actin, myosin SMC heavy chains, and vimentin, has been reported in later stages of atherosclerosis 32 and could be supported by the negative correlation between ATG16L1 and SMC-α-actin staining observed here. When considering this negative correlation with the fact that lipid-phagocytosing α-actin-positive SMC which are gaining CD68-positivity, that is, converted to macrophage foam cells, will retain their α-actin positivity, 30 we can infer that our finding of a positive correlation between the areas of ATG16L1-positivity and the areas of Oil Red O positivity (neutral lipid content) and CD68-positive macrophages reflects rather the presence of ATG16L1 in monocytederived macrophages than in SMC-derived macrophages.…”
Section: Discussionsupporting
confidence: 84%
“…consistent with autophagosomes were reported in VSMCs within atherosclerotic lesions (16) and atheromas (17) in humans and animal models. Subsequent studies in animal models of cardiovascular disease, using transgenic animals overexpressing labeled autophagic proteins (e.g., GFP-LC3) to monitor autophagic activity, similarly reported evidence of autophagy in VSMCs (18).…”
Section: Autophagic Activity In All Cardiovascular Cell Typesmentioning
confidence: 94%